2014
DOI: 10.1002/2014gl062009
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐scale spectral break of solar wind turbulence at high and low beta

Abstract: The power spectrum of magnetic fluctuations in the solar wind at 1 AU displays a break between two power laws in the range of spacecraft-frame frequencies 0.1 to 1 Hz. These frequencies correspond to spatial scales in the plasma frame near the proton gyroradius ρi and proton inertial length di. At 1 AU it is difficult to determine which of these is associated with the break, since and the perpendicular ion plasma beta is typically β⊥i∼1. To address this, several exceptional intervals with β⊥i≪1 and β⊥i≫1 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
184
5
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 163 publications
(220 citation statements)
references
References 68 publications
30
184
5
1
Order By: Relevance
“…Howes et al 2011;Franci et al 2015a). Note however that recent observational (Chen et al 2014) and numerical (Cerri et al 2016;Franci et al 2016) investigations suggest that the quantitative agreement with KAW predictions is fulfilled better at high ( 1) than low beta; this aspect will be the subject of a forthcoming study.…”
Section: T H E O R E T I C a L P R E D I C T I O Nmentioning
confidence: 82%
“…Howes et al 2011;Franci et al 2015a). Note however that recent observational (Chen et al 2014) and numerical (Cerri et al 2016;Franci et al 2016) investigations suggest that the quantitative agreement with KAW predictions is fulfilled better at high ( 1) than low beta; this aspect will be the subject of a forthcoming study.…”
Section: T H E O R E T I C a L P R E D I C T I O Nmentioning
confidence: 82%
“…Finally, the measured ion-scale spectral break can be compared to the expected dispersive scale for the transition from Alfvénic to kinetic Alfvén turbulence. Chen et al (2014a) examined periods of extreme β i so that the various ion scales could be distinguished, and found that for β i 1 the break occurs close to the ion gyroscale (kρ i ∼ 1), which is indeed the dispersive scale for Alfvénic turbulence, but at β i 1 it occurs at the ion inertial length (kd i ∼ 1). This latter result remains to be explained, but one possibility is the presence of a significant k component in low-β i turbulence (Boldyrev et al 2015).…”
Section: Phenomenological Models Of Kinetic Range Turbulencementioning
confidence: 99%
“…Šafránková et al (2015) have shown that a transition between MHD and kinetic ranges (break 2) scales with the ion thermal gyroradius R g . On the other hand, Chen et al (2014a) argued that the characteristic length depends on the plasma β being proportional to R g in a high-beta plasma, whereas the inertial length determines the break frequency in the low-beta solar wind. Since a majority of our events occurred in the moderateor high-beta solar wind, we followed the suggestion of Šafránková et al (2015) and used the proton thermal gyroradius, R g ,computed from the propagated Wind magnetic field and the ion thermal speed, V th ,for a determination of the gyrostructure frequency, f g :…”
Section: Scaling Of Psds In Thedownstream Regionmentioning
confidence: 99%
“…A spectral break around k 1 i  » (where i  is the ion thermal gyroradius) or kd i ≈1 (where d i is the ion inertial length) marks the end of the inertial range and suggests a possible initiation of kinetic dissipation processes at ion scales, while turbulent cascade continues to operate toward smaller scales up to electron gyroradius(e.g., Alexandrova et al 2009Alexandrova et al , 2012Chen et al 2014a).…”
Section: Introductionmentioning
confidence: 99%